A graphene oxide membrane with self‐regulated nanochannels for the exceptionally stable bio‐oil dehydration. Issue 1 (29th August 2019) - Li, Gang; Ma, Shanhong; Yang, He; Fan, Shuanshi; Lang, Xuemei; Wang, Yanhong; Li, Wentao; Liu, Yuanzhi; Zhou, Liang
Abstract: The transport behaviors and nanochannel structures of a graphene oxide (GO) membrane were studied for pervaporation dehydration of bio‐oil with a high acidity and a complex composition. The GO membrane showed an unprecedentedly stable water flux of approximately 0.43 kg m −2 hr −1, with a water content of 97 wt% in the permeate throughout 70 hr of pervaporation testing at 30°C. Both the calculated activation energy for water permeation and X‐ray diffraction characterization results confirmed that the nanochannel structures of the GO membrane were temperature‐ and liquid media‐responsive. The molecular intercalation‐induced self‐regulation of the size of laminar nanochannels in the GO membrane was suggested to be primarily responsible for the significantly reduced membrane fouling and the exceptionally stable pervaporation performance for the GO membrane. The mechanistic insights into the nanochannel structures and antifouling properties would provide important inspiration for the design of novel highly fouling‐resistant membrane materials for practical applications.